Short and long term outcome of neonatal hyperglycemia in very preterm infants: a retrospective follow-up study - van Zwieten Paul HT; Smits-Wintjens Vivianne EHJ; van der Lugt N Margreth; Walther Frans J (BMC, 2010)
Abstract Background Hyperglycemia in premature infants is associated with increased morbidity and mortality, but data on long-term outcome are limited. We investigated the effects of neonatal hyperglycemia (blood glucose ≥ 10 mmol/l, treated with insulin for ≥ 12 hours) on growth and neurobehavioral outcome at 2 years of age. Methods Retrospective follow-up study at 2 years of age among 859 infants ≤32 weeks of gestation admitted to a tertiary neonatal center between January 2002 and December 2006. Thirty-three survivors treated with insulin for hyperglycemia and 63 matched controls without hyperglycemia were evaluated at a corrected age of 2 years. Outcome measures consisted of growth (weight, length, and head circumference) and neurological and behavioural development. Results 66/859 (8%) infants ≤ 32 weeks of gestation developed hyperglycemia. Mortality during admission was 27/66 (41%) in the hyperglycemia group versus 62/793 (8%) in those without hyperglycemia (p < 0.001). Mortality was higher in infants with hyperglycemia with a birth weight ≤1,000 gram (p = 0.005) and/or gestational age of 24-28 weeks (p = 0.009) than in control infants without hyperglycemia. Sepsis was more prominent in infants with hyperglycemia and a birth weight of >1,000 gram (p = 0.002) and/or gestational age of 29-32 weeks (p = 0.009) than in control infants without hyperglycemia. Growth at 2 years of age was similar, but neurological and behavioural development was more frequently abnormal among those with neonatal hyperglycemia (p = 0.036 and 0.021 respectively). Conclusions Mortality was higher in very preterm infants with hyperglycemia treated with insulin during the neonatal period. At 2 years of age survivors showed normal growth, but a higher incidence of neurological and behavioural problems. Better strategies to manage hyperglycemia may improve outcome of very preterm infants.